2007
DOI: 10.1021/bc700152j
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Synthesis of Azido-Terminated Heterobifunctional Poly(ethylene glycol)s for “Click” Conjugation

Abstract: New azido-terminated heterobifunctional poly(ethylene glycol) (PEG) derivatives having primary amine and carboxyl end groups, (Azide-PEG-NH 2 and Azide-PEG-COOH, respectively) were synthesized with high efficiency. An alpha-allyl-omega-hydroxyl PEG was prepared as the first step to Azide-PEG-X (X = NH 2 and COOH) through the ring-opening polymerization of ethylene oxide (EO) with allyl alcohol as an initiator, followed by two-step modification of the hydroxyl end to an azido group. To introduce primary amino o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 35 publications
5
100
0
Order By: Relevance
“…30 For example, Kataoka and coworkers recently reported the synthesis of heterobifunctional PEG derivatives, having for example a primary amine or carboxylic acid group at one chain end, and an azide group at the other chain end. 31 Such functional PEGs are expected to have significant versatility in click chemistry, due to the mild reaction conditions used (aqueous buffers) and the high degree of chemoselectivity of the reaction. 31 The scope of click chemistry is not limited to the reaction of azides with terminal alkynes.…”
Section: Pegylated Drugs: Linear Peg Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…30 For example, Kataoka and coworkers recently reported the synthesis of heterobifunctional PEG derivatives, having for example a primary amine or carboxylic acid group at one chain end, and an azide group at the other chain end. 31 Such functional PEGs are expected to have significant versatility in click chemistry, due to the mild reaction conditions used (aqueous buffers) and the high degree of chemoselectivity of the reaction. 31 The scope of click chemistry is not limited to the reaction of azides with terminal alkynes.…”
Section: Pegylated Drugs: Linear Peg Conjugatesmentioning
confidence: 99%
“…31 Such functional PEGs are expected to have significant versatility in click chemistry, due to the mild reaction conditions used (aqueous buffers) and the high degree of chemoselectivity of the reaction. 31 The scope of click chemistry is not limited to the reaction of azides with terminal alkynes. For example, Bertozzi and coworkers 32 introduced Staudinger ligation reactions as a modified version of the classical Staudinger reaction, where an azide and phosphine react to give a primary amine and phosphine oxide.…”
Section: Pegylated Drugs: Linear Peg Conjugatesmentioning
confidence: 99%
“…1 The most common route to these hetero-bifunctional PEG relies on anionic polymerization of ethylene oxide from functional initiators followed by post-modification of the terminal hydroxyl group. [9][10][11][12][13][14] Other techniques include the modification of commercially available, but expensive, modified PEG molecules [15][16][17] or the sequential and unsymmetrical alteration of end hydroxyl groups of linear PEG. In particular, the use of tosylate activating groups was reported by Mahou and Wandrey 18 for the generation of diverse heterotelechelic PEG oligomers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that heterobifunctional PEG can be fabricated through polymer reactions starting from hydroxyl-terminated PEG [10][11][12][13][14][15]. For example, Kataoka's group [12][13][14] has reported many kinds of heterofunctional PEG by ring-opening polymerization of ethylene oxide (EO) with the derivative of alcohol such as allyl alcohol, 2-(tetrahydro-2H-pyran-2-yloxy)ethanol and 3,3-diethoxypropanol et al as initiator, followed by several steps of modification to obtain the final functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kataoka's group [12][13][14] has reported many kinds of heterofunctional PEG by ring-opening polymerization of ethylene oxide (EO) with the derivative of alcohol such as allyl alcohol, 2-(tetrahydro-2H-pyran-2-yloxy)ethanol and 3,3-diethoxypropanol et al as initiator, followed by several steps of modification to obtain the final functional groups. Owing to its high selectivity, mild reaction conditions, high yields and few by-products, the click reaction has rapidly become one of the most popular reactions to date.…”
Section: Introductionmentioning
confidence: 99%